Environmental aspects of molecular composition of humic acids isolated from lake sediments of a permafrost-affected area of the Arctic - Guzeva, Alina V.; Krylova, Ekaterina A.; Fedorova, Irina V. (Polish Polar Research, 2021)
Humic substances are ubiquitous in terrestrial and aquatic ecosystems. Humic acids (HAs) actively interact with organic and inorganic components of lake sediments. This interaction depends on the molecular structure and elemental composition of HAs. The presented research focuses on the investigation of the composition and molecular structure of humic acids isolated from lakes located in the Lena Delta in the Russian Arctic. The findings of the research are needed to estimate the potential capacity of humic acids to bind microelements, particularly toxic metals, in stable compounds. Surface sediment samples (0–10 cm) were collected from 8 lakes by Van Veen grab during the summer period of the “Expedition LENA 2019”. We analyzed elemental composition of the HAs samples. The results showed that the studied HAs of lake sediments are characterized by low nitrogen content and prevalence of aliphatic fragments in their molecular structure. Furthermore, it was found that the studied humic acids are less mature, showing mineralization processes dominant over humification, and have relatively low potential to complexation compared with soils of the Lena Delta as well as lake sediments of territories with more boreal climate conditions.